1998
DOI: 10.1037/0033-2909.123.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Situation models in language comprehension and memory.

Abstract: This article reviews research on the use of situation models in language comprehension and memory retrieval over the past 15 years. Situation models are integrated mental representations of a described state of affairs. Significant progress has been made in the scientific understanding of how situation models are involved in language comprehension and memory retrieval. Much of this research focuses on establishing the existence of situation models, often by using tasks that assess one dimension of a situation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
1,625
6
59

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,139 publications
(1,758 citation statements)
references
References 166 publications
(246 reference statements)
68
1,625
6
59
Order By: Relevance
“…Direct support for this hypothesis came from an experiment in which participants' recognition memory was tested immediately after reading a temporal reference sentence. Information presented just before the temporal reference was recalled less well when the temporal reference indicated a time shift than when no time shift occurred (See also Zwaan, 1996, Rinck & Bower, 2000, and Bower & Rinck, 2001, and see Zwaan & Radvansky, 1998 for a review of related effects). Together, these results support the theory's claim that event segmentation is a form of cognitive control, modulating cognitive processing and memory maintenance.…”
Section: Causes and Consequences Of Segmentation In Story Understandingmentioning
confidence: 99%
“…Direct support for this hypothesis came from an experiment in which participants' recognition memory was tested immediately after reading a temporal reference sentence. Information presented just before the temporal reference was recalled less well when the temporal reference indicated a time shift than when no time shift occurred (See also Zwaan, 1996, Rinck & Bower, 2000, and Bower & Rinck, 2001, and see Zwaan & Radvansky, 1998 for a review of related effects). Together, these results support the theory's claim that event segmentation is a form of cognitive control, modulating cognitive processing and memory maintenance.…”
Section: Causes and Consequences Of Segmentation In Story Understandingmentioning
confidence: 99%
“…Research on text comprehension (e.g., Kintsch, 1998) has shown that comprehenders not only construct a deep 'situation model' (Zwaan and Radvansky, 1998) to represent what the discourse is about, but also keep track of what has been said at a somewhat more superficial, propositional level, often referred to as the 'textbase' (Kintsch, 1998). In terms of these two levels of representation, note that "the girl" in (1b) not only sensibly refers to two suitable entities in the situation model, but also indexes (or 'resonates' with, Myers and O'Brien, 1998) two recently activated memory tokens of the concept girl, regardless of their suitability.…”
Section: The Referentially Induced Frontal Negativity (Nref Effect)mentioning
confidence: 99%
“…To come to a common understanding, interlocutors need to align their situation models, which are multi-dimensional representations containing information about space, time, causality, intentionality and currently relevant individuals [4][5][6]. The success of conversations depends considerably on the extent to which the interlocutors represent the same elements within their situation models (e.g.…”
Section: Problems Posed By Dialoguementioning
confidence: 99%